Electrical characterization of GaN-based Schottky diodes - Muhamad Nursharil Zaini. (2009)
Gallium nitride (GaN) based Schottky diodes with different contact diameters of 0.8mm, 1mm and 1.3mm have been made by physical vapour deposition of (Electron-Beam) metal contacts onto a gallium nitride on sapphire (Al2O3) and gallium nitride on silicon wafers. A graphical user interface based on LabVIEW software was developed to control a capacitance-voltage analyzer (Keithley 590) for real-time acquisition, display and rapid frame transfer of high data via a General Purpose Instrumentation Bus (GPIB). The program, written using dataflow programming, mimics the capabilities of the measurement equipment. Data acquisition is triggered by the user at the interface with the acquired data automatically displayed and the data stored or deleted at the user's discretion permitting detailed data analysis and display using software packages such as ORIGIN. Capacitance-voltage (C-V) and current-voltage (I-V) measurements were carried out using a C-V analyzer and a semiconductor parameter analyzer (HP 4155A), respectively highlighted the diminishing dependence of contact area on the barrier height and donor concentration, both which follow basic understanding of device physics. I-V analysis shows that although GaN/Si devices have much higher forward current, it also has a significantly high reverse leakage current that needs to be addressed by either improving the fabrication steps or by passivation of the surface. High reverse breakdown voltage that is inline with other reports had been observed. Also significant capacitance increases were observed at low test frequencies (100 KHz) highlighting the influence of stray capacitances, interface charges, deep-level traps and series resistances.